Effect of Prehospital Induction of Mild Hypothermia on 3‐Month Neurological Status and 1‐Year Survival Among Adults With Cardiac Arrest: Long‐Term Follow‐up of a Randomized, Clinical Trial. Issue 3 (11th March 2015) - Maynard, Charles; Longstreth, W. T.; Nichol, Graham; Hallstrom, Al; Kudenchuk, Peter J.; Rea, Thomas; Copass, Michael K.; Carlbom, David; Deem, Steven; Olsufka, Michele; Cobb, Leonard A.; Kim, Francis
Abstract : Background: Randomized trials of prehospital cooling after cardiac arrest have shown that neither prehospital cooling nor targeted temperature management differentially affected short‐term survival or neurological function. In this follow‐up study, we assess the association of prehospital hypothermia with neurological function at least 3 months after cardiac arrest and survival 1 year after cardiac arrest. Methods and Results: There were 508 individuals who were discharged alive from hospitals in King County, Washington; 373 (73%) were interviewed by telephone 123±43 days after the initial event. Overall, 59% of the treatment group and 58% of the control group had Cerebral Performance Category (CPC) 1 or 2 ( P =0.70), and 50% of the treatment group and 49% of the control group had slight disability or better by the Modified Rankin Scale (MRS; ( P =0.35). One‐year survival was 87% in the treatment group and 84% in the control group ( P =0.42). Of those with CPC 1 at hospital discharge, 68% had CPC 1 or 2 at follow‐up, and 59% had MRS of slight disability or better. Of 41 patients with CPC 3 or 4 at discharge, only 12% had CPC 2 at follow‐up, and just 5% had MRS of slight disability or better. One‐year survival was 92% for CPC 1 at discharge, but only 40% for CPC 4. Conclusion: In addition to excellent survival, patients who had good neurological function at discharge continued to have good function at least 3 months after the event. Clinical Trial Registration: URL: Clinicaltrials.gov. Unique identifier: NCT00391469